2022
DOI: 10.1007/s40259-022-00536-8
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Reactions to COVID-19 Vaccines: Risk Factors, Frequency, Mechanisms and Management

Abstract: Conventional vaccines have been widely studied, along with their risk of causing allergic reactions. These generally consist of mild local reactions and only rarely severe anaphylaxis. Although all the current COVID-19 vaccines marketed in Europe have been shown to be safe overall in the general population, early post-marketing evidence has shown that mRNA-based vaccines using novel platforms (i.e., lipid nanoparticles) were associated with an increased risk of severe allergic reactions as compared to conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 92 publications
2
42
0
1
Order By: Relevance
“…The role of vaccination was shown previously during previous COVID-19 waves as it improved maternal and fetal outcomes by reducing the severity of COVID-19 [8]. Vaccination has been shown to reduce the incidence of pneumonia and ARDS [8,20], which can cause lifethreatening hypoxemia and necessitate advanced resuscitation and, in some cases, cesarean delivery for fetal distress or maternal life-saving [8]. This may explain why vaccination allowed lower rates of cesarean deliveries and better maternal and fetal outcomes [8,21].…”
Section: Discussionmentioning
confidence: 77%
“…The role of vaccination was shown previously during previous COVID-19 waves as it improved maternal and fetal outcomes by reducing the severity of COVID-19 [8]. Vaccination has been shown to reduce the incidence of pneumonia and ARDS [8,20], which can cause lifethreatening hypoxemia and necessitate advanced resuscitation and, in some cases, cesarean delivery for fetal distress or maternal life-saving [8]. This may explain why vaccination allowed lower rates of cesarean deliveries and better maternal and fetal outcomes [8,21].…”
Section: Discussionmentioning
confidence: 77%
“…There is consensus in the literature that the incidence of HSRs and anaphylaxis caused by mRNA-LNP vaccinations is increased relative to that of traditional vaccines. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Taken the ~1.3 anaphylaxis/million out of >25 million recipients of flu vaccines, 44 as reference, the extent of increase is in the 3-400-fold range (STable 2). Nevertheless, this potentially lethal side effect is still considered as very rare, and its occurrence is further decreasing with time, as precautions are increased.…”
Section: Discussionmentioning
confidence: 99%
“…Since the mRNA-LNP vaccines include polyethylene glycol (PEG) as an excipient, allergy to PEG has been proposed as the mechanism of anaphylaxis. However, over time, it has been shown that the overwhelming majority of these reactions are not IgE-mediated classic type I allergies against PEG, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] leaving the underlying cause unclear. Among the studies addressing this puzzle, the possible role of anti-PEG antibodies (Abs) was raised, 1,17,19,20 but conclusive experimental or clinical evidence was not presented to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the benefit-risk profile of these vaccines was proven to be largely favorable in the general population, evidence in special cohorts initially excluded from the pivotal trials, such as pregnant and breastfeeding women, is still limited. The vaccines and particularly mRNA vaccines used in our population may induce additional cellular or humoral immune regulation, including T helper cell responses and germinal center responses, and form relevant memory cells, greatly improving their efficiency [14]. However, in pregnancy, there is a shift in Th1/Th2 that may trouble the immune response after infection [15] and may reduce the efficacy of vaccination [16].…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%